A Case of Chronic Masticator Space Abscess - Udaka, Tsuyoshi; Yoshida, Masafumi; Fujiyoshi, Tatsuya; Makishima, Kazumi; Hiraki, Nobuaki; Shimizu, Takashi (Nippon Jibi Inkoka Gakkai Kaiho, 2001)
Different neoplasms and infections are known to involve the masticator space, but pathological diagnosis and treatment of these lesions are not always simple due to anatomical complexity. We treated a 66-year-old man with an abscess in the nasopharyngeal masticator space. Physical and CT findings resembled those of a neoplastic lesion because the onset dated back 5 years and the patient was lacking in notable signs of infection. Surgery through the maxillary sinus to the lesion enabled us to confirm its pathology and drain pus, with subsequent cure. We noted periodontal infection of the mandibular molars accompanied with osteomyelitis as a cause of this abscess, so infected molars were extracted 13 days after surgery. The infection had spread upward along the mastication muscles, resulting in an abscess in both the upper masseter muscle and the lower temporalis muscle. Based on a review of the literature, most abscesses in the masticator space originate from the mandibular molar, while the most impressive physical finding varied between the submandibular region and temporal fossa, as did its acute or chronic clinical course. Such clinical manifestations appear to reflect the pattern of infection spread along the muscles of mastication and a pattern involving adjacent spaces. We emphasize diagnostic significance when assessing findings for each mastication muscle and mandibular bone depicted using computed tomography, magnetic resonance imaging, and bone-scan technetium.